Elements of Integrating Traditional and Complementary Medicine into Primary Healthcare: A Systematic Review - Ahmad Negahban; Mohammadreza Maleki; Alireza Abbassian (Journal of Clinical and Diagnostic Research, 2018)
Introduction: Patients prefer primary healthcare to include conventional medical services together with complementary medicine. The process of integration can be a stressful process for providers of both complementary and modern medical services. Aim: This study aimed to determine the elements of integrating traditional and complementary medicine into primary healthcare. Materials and Methods: This systematic review searched the Web of Science, Scopus, PubMed, Ovid, and EMBASE from January 2000 to February 2017. Data were analysed by the content analysis method. Results: The search of databases resulted in 1391 records. The duplicates were removed, titles and abstracts were screened, and irrelevant records were excluded. Finally, 25 studies were included and five elements identified that are important for integrating traditional and complementary medicine into primary health care. Eighteen studies addressed communication and collaboration, 12 studies addressed patient-centeredness, 12 studies addressed types of practice, 11 studies mentioned education and training, 8 studies mentioned policy and plan, 7 studies addressed financial support. Conclusion: Integrating traditional medicine into primary healthcare requires government support and policy-making. Communication, professional dealings, and training are important and influential in all stages of integration. Integrated services should be culturally acceptable and financially covered by insurance.